Non-domination, real freedom and basic income - Elgarte, Julieta
I explore the potentialities and limits of Philip Pettit's notion of non-domination as the core of a normative justification of basic income. I argue that if we find non-domination desirable for the reasons Pettit offers us as a proof of its value, then our concern to promote non- domination should only commit us to the erradication of domination. It cannot, as Pettit claims, commit us to the creation of new undominated options once domination has been erradicated. What does do this job is another notion of freedom: real freedom, proposed by Philippe Van Parijs. Hence, I shall argue, non-domination can justify a basic income at subsistence level, while real freedom can justify the highest susteinable level of basic income.